Relação das práticas da avaliação de desempenho e o capital humano ao comportamento inovador - Grassi, Beatriz Salete Borssoi (2024)
Performance evaluation has the main purpose of evaluating the delivery of activities combined with the skills of an individual or a group of individuals with a focus on performance. Individual innovative behavior, being seen at the level of human capital, has become a relevant factor in the work environment, as it determines the survival and success of organizations. The objective of this study was to analyze the relationships between performance assessment practices and human capital and innovative behavior. For this, the variables were analyzed: performance assessment, innovative behavior and human capital and the value and specificity of individuals' knowledge. The research involved a sample of 133 interviewees, using a quantitative approach, with the formulation of hypotheses to support the literature review, analysis carried out through Structural Equation Modeling, using the Partial Least Squares method and use of software Smart PLS 4 (Partial Least Squares). The results found confirm and point to a positive influence on the relationship between Performance Assessment Practices in relation to Individual Innovative Behavior described in hypothesis 1, supporting the concepts found in the literature. The results of hypothesis 2, Human Capital in relation to Innovative Behavior also showed a positive influence when observing and analyzing the Human Capital Value and Specificity of Knowledge of individuals in a single variable. However, the research remained observations and analyzes observing the Human Capital Value and Specificity of Knowledge of individuals in two variables, as this allowed better results to be obtained, confirming a positive influence on the value of knowledge and a negative influence on the specificity of knowledge, or that is, Human Capital to the Value of Knowledge of individuals in relation to Individual Innovative Behavior confirmed a positive influence, the findings confirm the approaches in the literature; to Human Capital focused on the Specificity of Knowledge of individuals in relation to Individual Innovative Behavior, the influence was negative, diverging from the positions that the literature describes. It is concluded that the results found in performance assessment practices in relation to innovative behavior confirm the construction of the model construct described in hypothesis 1 in a significant way, where acceptance was obtained, however when analyzing Human Capital in relation to behavior innovative described in hypothesis 2, the construction of the proposed model construct had to be analyzed in two observable variables, related to the value and specificity of individuals' knowledge in relation to individual innovative behavior.